THE INFLUENCE OF SERVICE QUALITY, FOOD QUALITY AND PERCEIVED VALUE ON CUSTOMER SATISFACTION IN PADANG PAYAKUMBUAH - Aqilah, Khonsa Mumtaz; Aini, Husna N; Nuh, Ahmad; Eddy W, Finantyo (Universitas Indraprasta PGRI Jakarta, 2024)
The research titled